# |
ODE |
Mathematica |
Maple |
\[
{}[x^{\prime }\left (t \right )-7 x \left (t \right )+y \left (t \right ) = 0, y^{\prime }\left (t \right )-2 x \left (t \right )-5 y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+2 x \left (t \right )-3 y \left (t \right ) = t, y^{\prime }\left (t \right )-3 x \left (t \right )+2 y \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+44 x \left (t \right )+49 y \left (t \right ) = t, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+34 x \left (t \right )+38 y \left (t \right ) = {\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime \prime }\left (t \right )-3 x \left (t \right )-4 y \left (t \right ) = 0, y^{\prime \prime }\left (t \right )+x \left (t \right )+y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+2 y^{\prime }\left (t \right )-2 x \left (t \right )+2 y \left (t \right ) = 3 \,{\mathrm e}^{t}, 3 x^{\prime }\left (t \right )+y^{\prime }\left (t \right )+2 x \left (t \right )+y \left (t \right ) = 4 \,{\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+2 x \left (t \right )+31 y \left (t \right ) = {\mathrm e}^{t}, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+x \left (t \right )+24 y \left (t \right ) = 3]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+4 x \left (t \right )+3 y \left (t \right ) = t, y^{\prime }\left (t \right )+2 x \left (t \right )+5 y \left (t \right ) = {\mathrm e}^{t}]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right ) = n y \left (t \right )-m z \left (t \right ), y^{\prime }\left (t \right ) = L z \left (t \right )-m x \left (t \right ), z^{\prime }\left (t \right ) = m x \left (t \right )-L y \left (t \right )]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right )+y \left (t \right ) = 0, t y^{\prime }\left (t \right )+x \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )-7 x \left (t \right )+y \left (t \right ) = 0, y^{\prime }\left (t \right )-2 x \left (t \right )-5 y \left (t \right ) = 0]
\] |
✓ |
✓ |
|
\[
{}[x^{\prime }\left (t \right )+5 x \left (t \right )+y \left (t \right ) = {\mathrm e}^{t}, y^{\prime }\left (t \right )+3 y \left (t \right )-x \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[4 x^{\prime }\left (t \right )+9 y^{\prime }\left (t \right )+11 x \left (t \right )+31 y \left (t \right ) = {\mathrm e}^{t}, 3 x^{\prime }\left (t \right )+7 y^{\prime }\left (t \right )+8 x \left (t \right )+24 y \left (t \right ) = {\mathrm e}^{2 t}]
\] |
✓ |
✓ |
|
\[
{}[t x^{\prime }\left (t \right ) = t -2 x \left (t \right ), t y^{\prime }\left (t \right ) = t x \left (t \right )+t y \left (t \right )+2 x \left (t \right )-t]
\] |
✓ |
✓ |
|